Segregation of Children Who Migrate to the U.S. From Puerto Rico - Laosa, Luis M. (Education Policy Analysis Archives, 2001)
This study examined patterns of school segregation (ethnic/racial, linguistic, and socioeconomic) and other ecological characteristics of the schools that preadolescent children who migrate from Puerto Rico to the United States (New Jersey) attend in this country during the first two years following their arrival (N = 89 schools). The data show that Hispanics/Latinos are the majority of the student body in 43% of the schools; African Americans, in 30% of the schools; and European Americans, in 12% of the schools. Native speakers of Spanish are the majority of the student body in 29% of the schools. Approximately one half of the schools are in economically depressed, highly urbanized areas. Although the schools are on average large, 44% of them enroll above capacity. In most schools the majority of the student body is from economically impoverished families with low levels of parental education. There are, however, wide differences among the schools on each of these variables. Correlations show that the higher a student body's proportion of Hispanics/Latinos or native speakers of Spanish, the higher is the student body's proportion of pupils from economically impoverished households with low levels of parental education, and the higher the school's likelihood of being crowded and of being located in a poor inner-city area. Similarly, the higher a student body's proportion of African Americans, the higher is the student body's proportion of pupils from low-income families, and the higher the school's likelihood of being in a poor inner-city area. The findings are discussed with regard to implications for policy and hypotheses in need of research concerning possible consequences of school segregation for students' academic, linguistic, social, and emotional development. Also presented is a historical overview, to the present, and discussion of U.S. policies and judicial decisions concerning school segregation, with particular reference to segregation of Hispanics/Latinos.